2015
DOI: 10.1007/s11881-015-0101-3
|View full text |Cite
|
Sign up to set email alerts
|

Reading difficulties in Spanish adults with dyslexia

Abstract: Recent studies show that dyslexia persists into adulthood, even in highly educated and well-read people. The main characteristic that adults with dyslexia present is a low speed when reading. In Spanish, a shallow orthographic system, no studies about adults with dyslexia are available; and it is possible that the consistency of the orthographic system favours the reading fluency. The aim of this study was to get an insight of the reading characteristics of Spanish adults with dyslexia and also to infer the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 62 publications
5
26
0
3
Order By: Relevance
“…In an effort to improve on the validity of our method, a later study might follow other studies [ 23 , 26 ] by adding a self-report questionnaire, including items on reading-writing difficulties in daily life. The correlation between the score obtained in such a questionnaire and our screening scores might improve the discriminant power of the present procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an effort to improve on the validity of our method, a later study might follow other studies [ 23 , 26 ] by adding a self-report questionnaire, including items on reading-writing difficulties in daily life. The correlation between the score obtained in such a questionnaire and our screening scores might improve the discriminant power of the present procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The results with Spanish-speaking adults are similar: Spanish university students have spelling problems, must constantly checking the orthography, and easily confuse letters when writing [ 22 ]. They also experience trouble in phonological awareness and reading speed [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies [48,49] revealed that dyslexia persists into adulthood. In general, these studies showed that Spanish adults with dyslexia present problems in reading words, pseudowords, reading comprehension, fluency, and reading motivation.…”
Section: Reading-related Cognitive Deficits In Dyslexia and Emotionalmentioning
confidence: 99%
“…Promising results have shown of children who go through such intervention programs in the early stages [ 24 ] proving improvement in reading performance as well as reduction in anxiety [ 25 ]. Though these techniques help, dyslexia still does persist into adulthood [ 26 ].…”
Section: Introductionmentioning
confidence: 99%